When Workload Meets Emotional Labor: Service Performance in Hotel Rooms Division - ER Ummi Kalsum; Ananta Budhi Danurdara; Anwari Masatip (International Journal of Applied Business and International Management, 2025)
Employees in hotel rooms division operate under high operational pressure while maintaining continuous interaction with guests, making workload and emotional labor critical determinants of service performance. This study examines how workload and emotional labor influence service performance through job satisfaction among front office and housekeeping employees in Indonesian hotels. Grounded in the Job Demands–Resources framework, a quantitative approach was employed using survey data from 238 employees, analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that workload and emotional labor have negative and significant effects on both service performance and job satisfaction. Workload demonstrates a stronger effect compared to emotional labor, indicating that operational pressure functions as the primary constraint in rooms division work. Job satisfaction has a positive and significant effect on service performance and represents the strongest predictor in the model. Furthermore, job satisfaction partially mediates the relationships between job demands and service performance, indicating that performance is shaped by both direct operational constraints and employees’ psychological responses. These findings highlight the importance of integrating operational and emotional demands in managing service performance in hotel rooms division